Thermal processing of biomass into high-calorific solid composite fuel; Journal of Analytical and Applied Pyrolysis; Vol. 124 - Tabakaev R. B. Roman Borisovich; Shanenkov I. I. Ivan Igorevich; Kazakov A. V. Aleksandr Vladimirovich; Zavorin A. S. Aleksandr Sergeevich (2017, 2017)
Title screen